Exploring Learning Styles and Oral Communication Strategies and their Relationship with Emotional Intelligence of EFL Learners - Ali Roohani; Rezvan Etesami; Azizullah Mirzaei (Teaching English Language, 2020)
This study explored Learning Styles (LSs) and Oral Communication Strategies (OCSs) among the Iranian learners of English with high and low Emotional Quotient (EQ). Moreover, it looked into the association between emotional intelligence (EI) with four LSs and OCSs in high and low EQ groups. Three questionnaires were employed to gather data from 108 participants from Shahrekord, Isfahan, and Payam Noor universities. Descriptive and correlational statistics were utilized to analyze the data. The results of descriptive statistics showed that the learners with high EQ favored visual and kinesthetic LSs more, whereas the learners with low EQ favored kinesthetic and auditory LSs. The high EQ group preferred accuracy-oriented and negotiating for meaning strategies more, while the low EQ group preferred word-oriented and scanning strategies. Besides, strategies of attempting to think in English and abandoning the message were the least frequent strategies. Correlational analysis also indicated that EI did not significantly correlate with any of the learners' LSs, nor did it correlate with the OCSs in the high EQ group. However, there were positive correlations between the learners' EI and OCSs for dealing with speaking problems in the low EQ group. The findings have implications for foreign language learning.